A review of stereotactic body radiotherapy – is volumetric modulated arc therapy the answer? - Sapkaroski, Daniel (J Med Radiat Sci, 2015)
Stereotactic body radiotherapy (SBRT) is a high precision radiotherapy technique used for the treatment of small to moderate extra-cranial tumours. Early studies utilising SBRT have shown favourable outcomes. However, major disadvantages of static field SBRT include long treatment times and toxicity complications. Volumetric modulated arc therapy (VMAT) and intensity modulated radiotherapy (IMRT) may potentially mitigate these disadvantages. This review aims to assess the feasibility of emerging VMAT and IMRT-based SBRT treatment techniques and qualify which offers the best outcome for patients, whilst identifying any emerging and advantageous SBRT planning trends. A review and synthesis of data from current literature up to September 2013 was conducted on EMBASE, Medline, PubMed, Science Direct, Proquest central, Google Scholar and the Cochrane Database of Systematic reviews. Only full text papers comparing VMAT and or IMRT and or Static SBRT were included. Ten papers were identified that evaluated the results of VMAT/IMRT SBRT. Five related to medically inoperable stage 1 and 2 non-small-cell lung cancer (NSCLC), three to spinal metastasis, one related to abdominal lymph node malignancies, with the final one looking at pancreatic adenocarcinoma. Overall treatment times with VMAT were reduced by 66–70% for lung, 46–58% for spine, 42% and 21% for lymph node and pancreatic metastasis respectively, planning constraints were met with several studies showing improved organs at risk sparing with IMRT/VMAT to static SBRT. Both IMRT and VMAT were able to meet all planning constraints in the studies reviewed, with VMAT offering the greatest treatment efficiency. Early clinical outcomes with VMAT and IMRT SBRT have demonstrated excellent local control and favourable survival outcomes.